(untitled) (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: Piroxicam is class II drug and has low oral bioavailability owing to low aqueous solubility. Long-term administration of piroxicam is reported to produce gastrointestinal toxicity. The objective of this study was to improve the permeation of piroxicam by incorporating as piroxicam loaded solid lipid nanoparticles (pirox-SLNs) into a transdermal patch. Method: Pirox-SLN’s (average particle size 248.87 ± 6.481 nm and entrapment efficiency 84.48% ± 1.08%) upon optimization, were prepared by pre-emulsion sonication method and were incorporated into ethyl cellulose and polyvinyl pyrrolidone matrix patch prepared by solvent evaporation method. Results& Discussion: The prepared transdermal patches were evaluated for thickness, weight variation, flatness, folding endurance, and drug content which were found to 0.31 ± 0.04 mm, 0.17 ± 0.03 g, 99.5% ± 0.3%, 35 ± 1.34 and 95.74 ± 0.4, respectively. Ex-vivo skin permeation of the prepared formulation was studied on rat skin and the drug release from patch incorporated with SLNs was found 66.6% up to 24 h, significantly less as compared to plain piroxicam patch having release of 88.01%, however, the slow release from the SLN patch was attributed due to slow release of the drug from SLN. Ex-vivo skin permeation studies on pirox-SLN containing patches showed satisfactory flux (17.16 μg/cm2/h) compared with that of plain piroxicam patches (4.6 μg/cm2/h). The skin irritation test showed that the prepared transdermal patch were free of skin irritants. Conclusion: It was concluded that SLN’s can be successfully used as a carrier for enhancing transdermal permeation of piroxicam and thus the bioavailability.